Contention and trust in cities and states - Hanagan, Michael; Tilly, Chris (Springer Netherlands, 2011)
Cities and nation-states have co-existed uneasily throughout human history. At times fused, at other times opposed, at still other times hierarchically linked, they have been crucibles of identity and social and political action. Today?s globalization re-elevates the importance of cities, but contrary to what is often claimed, also sustains the importance of nation-states in transformed ways. Contention and Trust in Cities and States explores cities and nation-states throughout history and around the world, bringing together the research of top scholars. It takes as a jumping-off point the work of the late Charles Tilly, but proceeds varied topics ranging from how today's drug cartels undermine nation-states to how cities, nation-states, and empires treated religious minorities in the middle of the last millennium. Threaded throughout are themes of city-state relations, trust networks and commitment, democracy and inequality, and the importance of historical legacies in shaping state structures, practices, and capacities. Political scientists, sociologists, geographers, urbanists, historians and others concerned with how power and trust play out in cities and nation-states will find this a provocative and valuable collection.